(untitled) (Journal of actual problems of jurisprudence, 2020)
Since ancient times, social consciousness excited by the phenomenon of euthanasia. In the modern period, the ethical, medical and legal problems of euthanasia are topical issues. Euthanasia is one of the main sections of thanatology – teachings about death. The main issue under discussions, is the question of legalizing euthanasia in the legislation of modern states. The purpose of the article is to analyze the current situation of this problem from the ethics, medicine and law points of view. The research applied modern scientific methods. A wide range of foreign sources and legislative acts of different countries is analyzed. A global debate on the expediency of legalizing euthanasia has been analyzed. The application of general scientific methods allowed us to compare the domestic and international methodology of work. The classifying of states based on the criterion of legalization or prohibition of euthanasia was conducted. The examples of the legal framework for the use of euthanasia in the Netherlands, Belgium, and the USA examine the problem of legal regulation of the euthanasia procedure. The problem of legal regulation of euthanasia is considered in conjunction with ethical and medical issues. As a result of the study, the conclusions were reached. The article identifies possible consequences for the medical ethics, taking into account the legalization of euthanasia in a growing number of countries. Particularly the assumption of how medical codes of ethics should adapt to the current state of the problem is grounded. Key words: rights, euthanasia, death, medical ethics, law, legalization, prohibition.